Lipschitz Estimates for Fractional Multilinear Singular Integral on Variable Exponent Lebesgue Spaces - Hui-Ling Wu; Jia-Cheng Lan (Abstract and Applied Analysis)
We obtain the Lipschitz boundedness for a class of fractional multilinear operators with rough kernels on variable exponent Lebesgue spaces. Our results generalize the related conclusions on Lebesgue spaces with constant exponent.